A Comprehensive Review of the Thermophysical Properties of Energetic Ionic Liquids - Aishorjo Bablee; Ananda Amarasekara; Jorge Gabitto; Ariful Bhuiyan; Nabila Shamim (Energies)
Energetic ionic liquids (EILs) have various industrial applications because they release chemically stored energy under certain conditions. They can avoid some environmental problems caused by traditionally used toxic fuels. EILs, which are environmentally friendly and safer, are emerging as an alternative source for hypergolic bipropellant fuels. This review focuses on the crucial thermophysical properties of the EILs. The properties of imidazolium and triazolium-based ionic liquids (ILs) are discussed here. The thermophysical properties addressed, such as glass transition temperature, viscosity, and thermal stability, are critical for designing EILs to meet the need for sustainable energy solutions. Imidazolium-based ILs have tunable physical properties making them ideal for use in energy storage while triazolium-based ILs have thermal stability and energetic potential. As a result, it is important to understand and compile thermophysical properties so they can help researchers synthesize tailored compounds with desirable characteristics, advancing their application in energy storage and propulsion technologies.